With $92 dollars you could buy 18 ice cream sandwiches.
Answer:
x = -4, y = 3/2
Step-by-step explanation:
simplify the 1st equation by dividing each term by 4 to get:
x + 2y = -1
-5x + 2y = 23
Subtract to get: 6x = -24
x = -4
find 'y': 2y - 5(-4) = 23
2y + 20 = 23
2y = 3
y = 3/2
Answer:
x can be cancelled
Step-by-step explanation:
we are given
![\frac{4x^3-10x^2+6x}{2x^3+x^2-3x}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%5E3-10x%5E2%2B6x%7D%7B2x%5E3%2Bx%5E2-3x%7D)
Firstly, we will factor numerator and denominator
and then we can factor it
![4x^3-10x^2+6x=2x(2x^2-5x+3)](https://tex.z-dn.net/?f=4x%5E3-10x%5E2%2B6x%3D2x%282x%5E2-5x%2B3%29)
![4x^3-10x^2+6x=2x(2x+1)(x-3)](https://tex.z-dn.net/?f=4x%5E3-10x%5E2%2B6x%3D2x%282x%2B1%29%28x-3%29)
now, we can factor denominator
![2x^3+x^2-3x=x(2x^2+x-3)](https://tex.z-dn.net/?f=2x%5E3%2Bx%5E2-3x%3Dx%282x%5E2%2Bx-3%29)
![2x^3+x^2-3x=x(x-1)(2x+3)](https://tex.z-dn.net/?f=2x%5E3%2Bx%5E2-3x%3Dx%28x-1%29%282x%2B3%29)
now, we can replace it
![\frac{4x^3-10x^2+6x}{2x^3+x^2-3x}=\frac{2x(2x+1)(x-3)}{x(x-1)(2x+3)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%5E3-10x%5E2%2B6x%7D%7B2x%5E3%2Bx%5E2-3x%7D%3D%5Cfrac%7B2x%282x%2B1%29%28x-3%29%7D%7Bx%28x-1%29%282x%2B3%29%7D)
we can see that
both terms are having x common
so, x can be cancelled
So,
x can be cancelled